2013
DOI: 10.1021/cs4001333
|View full text |Cite
|
Sign up to set email alerts
|

Mechanocatalytic Depolymerization of Dry (Ligno)cellulose As an Entry Process for High-Yield Production of Furfurals

Abstract: Driven by mechanical forces, the acid-catalyzed depolymerization of solid biomass completely overcomes the problems posed by the recalcitrance of lignocellulose. The solid-state reaction leads to water-soluble oligosaccharides, which display higher reactivity than cellulose and hemicellulose. Here, we show that water-soluble oligosaccharides are useful feedstock for the high-yield production of 5-hydroxymethylfurfural (HMF) and furfural in biphasic reactors. This is because they readily undergo hydrolysis upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 49 publications
(125 reference statements)
3
73
0
1
Order By: Relevance
“…Moreover, a significant enhancement of the furfural yield as well as the selectivity was achieved in the biphasic system (Table 2, entries 12 and 13). These results were consistent with the reported in literatures (Carrasquillo-Flores et al, 2013;Guerbuez et al, 2012). The addition of NaCl to the biphasic system can greatly improve the partitioning of furfural into the organic phase by altering the intermolecular bonding interactions between liquid components, thus increase the immiscibility between the aqueous phase and the organic phase (Nikolla et al, 2011).…”
Section: Influences Of Different Catalysts Co-solvents and Systems Osupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, a significant enhancement of the furfural yield as well as the selectivity was achieved in the biphasic system (Table 2, entries 12 and 13). These results were consistent with the reported in literatures (Carrasquillo-Flores et al, 2013;Guerbuez et al, 2012). The addition of NaCl to the biphasic system can greatly improve the partitioning of furfural into the organic phase by altering the intermolecular bonding interactions between liquid components, thus increase the immiscibility between the aqueous phase and the organic phase (Nikolla et al, 2011).…”
Section: Influences Of Different Catalysts Co-solvents and Systems Osupporting
confidence: 94%
“…Thereafter, water as well as some other solvents (ionic liquids and organic solvents) have been widely applied for the furfural synthesis under various conditions (Wei et al, 2011;Zhang et al, 2013). Recently, a new biorefining strategy for converting the biomass to the furan compounds by utilizing biphasic systems was proposed (Carrasquillo-Flores et al, 2013;Guerbuez et al, 2012). In biphasic systems, target products are transferred from the aqueous phase to the organic phase once produced, thus ceases interfering side reactions (Daengprasert et al, 2011;Ordomsky et al, 2013;Pagan-Torres et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…151 Dutta et al 152 converted sugarcane bagasse into ethoxymethylfurfural (EMF), a fuel additive, by using metal chlorides in DMA-LiCl and ionic liquids ([BMIM]Cl) with ethanol. In a first step, they obtained HMF yields of 42% from sugarcane bagasse in the presence of Zr(O)Cl 2 /CrCl 3 and using [BMIM]Cl as a solvent.…”
mentioning
confidence: 99%
“…Among its various applications, the mechanocatalysis of biomass has gained much attention because of its potential to be a green and practical pathway in biomass pretreatment. Lignocellulose can be more efficiently converted into sugars, alcohols, furfurals, and other biomassderived chemicals after being pretreated by mechanochemical processes [14,15]. Cellulose and lignin were ball milled after being mixed with acidic and basic solid catalysts, respectively, and it was found that the mechanocatalysis process could depolymerize the substrates and result in water-soluble fractions, since the β-1,4 glyosidic bond and β-O-4 linkage can be cleaved by a synergistic effect between the solid catalyst and mechanical forces [16−18].…”
Section: Effect Of Milling Durationmentioning
confidence: 99%